Synthesis and Anti-hyperglycaemic Study of Aryl Sulfonate Ester Conjugated 5-arylidene-thiazolidine-2,4-diones - Mehta, Mukul; Mahapatra, Manoj Kumar (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Diabetes mellitus, a lifestyle related global health crisis has rapidly engulfed the entire world. In the past, various thiazolidinedione derivatives have been successfully developed for management of diabetes. Materials and Methods: Herein, we report synthesis, characterization (1H-NMR, 13C-NMR and mass spectroscopy methods) of novel aryl sulfonyloxy-5-arylidene thiazolidine-2,4-dione analogues. Anti-hyperglycaemic action (Alloxan-induced method) was performed for evaluating the antidiabetic potential of the synthesized compounds. Docking analysis of the final compounds were carried out to reveal interactions with the active site pocket of enzymes like protein tyrosine phosphatase 1B, aldose reductase and peroxisome proliferator activated-γ. The synthesized compounds were further subjected to ADME (Absorption, Distribution, Metabolism, Elimination) prediction studies to prove their drug-like potential. Results: Compound 10 and 12 showed comparable reduction in blood sugar as that with pioglitazone. Docking studies helped in understanding the probable binding mode inside the binding cavity of the concerned receptors. Conclusion: Aryl sulfonate esters with phenyl and chloro phenyl substituents were found to have superior anti-hyperglycaemic activity.
Keywords: ADME; Anti-hyperglycaemic; Aryl sulfonyloxy-5-arylidenethiazolidine-2,4-dione; Docking; Spectral characterization